Structural Classification Methodology and Assignment of General Shop Costs for the Industrial Company’s Production Cost - I. E. Mizikovskii (Учёт. Анализ. Аудит, 2021)
The paper describes the issues of improving the grouping and rearrangement of indirect costs of industrial companies, as well as their attribution to the production costs (works, services). Structural classification is one of the most urgent problems of accounting and calculation activities. This system involves the economically justified identification and subsequent systematization of indirect costs in the accounting information space and production management of an economic entity in the real sector of the transformation economy. The study goal is to develop a methodology that allows to reduce labor costs and improve the quality of the process. Also, it helps to raise the result of forming the production cost of an industrial company, improves the information base for making managerial decisions and economic strategies for the development of the company. The foundation of the theoretical and methodological basis of the research was the use of structural classification of costs based on dichotomous relations, observations, verification, semantic and multifactorial types of economic analysis, graphical formalization, decomposition. The author considered in detail the existing approaches to the identification of indirect production costs and the model of their inclusion in the cost price. The implementation of the proposed methodology is aimed at ensuring greater efficiency of the accounting and calculation process and awareness of management decision-makers. The study results can be used by practical and scientific workers, state bodies staff in improving regulatory documents.